Growth and Production of Shallots (Allium cepa L. Aggregatum group) in Highlands with Organic Fertilizer Treatment - Simatupang, Lambok; Siregar, Rolan (PT FORMOSA CENDEKIA GLOBAL, 2025)
The objective of this study was to assess the growth and yield of upland shallots (Allium cepa L. Aggregatum group) with organic fertilizer treatments. A Factorial Randomized Block Design (RAK) with two factors and three replications was applied. The first factor was the application of eucalyptus leaf litter bokashi, with four levels: S0 (0 kg/plot), S1 (3 kg/plot), S2 (5 kg/plot), and S3 (7 kg/plot). The second factor was the application of liquid organic fertilizer (POC) from cow urine, with four levels: U0 (0 ml/plant), U1 (100 ml/plant), U2 (200 ml/plant), and U3 (300 ml/plant). The parameters measured included plant height (cm), leaf count (strands), fresh tuber weight per plot (g), and dry economic tuber weight per plot (g). The results indicated that the combination of eucalyptus leaf litter bokashi and cow urine POC had a significant effect on the growth and yield of shallots. The highest vegetative growth was recorded with a plant height of 49.82 cm at an organic fertilizer application rate of 3.52 kg/plot and POC of 100 ml/plant. The maximum number of leaves reached 46.09 strands with an organic fertilizer dose of 3.85 kg/plot and POC of 269 ml/plant. The highest fresh tuber weight per plot was 2,132.82 g with 4.44 kg/plot of organic fertilizer and 284 ml/plant of POC, while the maximum dry economic tuber weight per plot was 1,916.99 g at an organic fertilizer dose of 3.87 kg/plot and POC application of 295 ml/plant.